Students' Motivation in Learning English through Ubiquitous Learning (Video-Based Learning) - Azzahra, Ai Mulyani; Rochmawati, Rochmawati; Az Zahra, Houra (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the accessibility and flexibility of ubiquitous learning (u-learning) that influences students’ motivation in learning English. The participants were a cohort of 57 students enrolled in a one-year English program. U-learning uses seamless access to the materials that can be accessed anytime and anywhere. The data of the study were collected through a combination of observations, interview, and a likert scale based questionnaire. The observation was conducted in real-time interactions to observe students’ behaviors and engagement. While semi-structured interviews used to get deeper insights into their experiences, find the obstacles and benefits of u-learning implementation in English learning. While, the questionnaire used to know the intrinsic and extrinsic motivation. The analysis of the collected data revealed that the combination of u-learning and video-based learning significantly enhanced learner autonomy, engagement, and intrinsic motivation are fostering English language skills. The obstacles such as inconsistent internet access and other distractions were found. So, it is necessary to maximize the effectiveness of video-based learning in English learning. In addition, these findings emphasize the role of u-learning in fostering motivation in English language learning.Keywords: motivation, ubiquitous learning, video-based learning.